2018
DOI: 10.1021/acs.estlett.8b00081
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Methyl Mercury Net Degradation in Alder Swamps: The Role of Methanogens and Abiotic Processes

Abstract: Wetlands are common net producers of the neurotoxin monomethylmercury (MeHg) and are largely responsible for MeHg bioaccumulation in aquatic food-webs. However, not all wetlands net produce MeHg; notable exceptions are black alder (Alnus glutinosa) swamps, which net degrade MeHg. Here we report the mechanisms of MeHg demethylation in one such swamp (EHT), shown to be a sink for MeHg during four consecutive years. The potential demethylation rate constant (k d) in soil incubations was ∼3 times higher in the dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 48 publications
1
48
1
Order By: Relevance
“…To the best of our knowledge, only one recent study has been published that fits this description. In this work, Kronberg et al 2018 showed that methanogens are important contributors to OD in a wetland ecosystem known to be a FACETS | 2018 | 3: 858-879 | DOI: 10.1139/facets-2018-0015 862 facetsjournal.com sink for MeHg. Together with previous work on methanogens, this finding frames methane cycling microbes as key players in controlling MeHg levels in the environment.…”
Section: Grégoire and Poulainmentioning
confidence: 84%
“…To the best of our knowledge, only one recent study has been published that fits this description. In this work, Kronberg et al 2018 showed that methanogens are important contributors to OD in a wetland ecosystem known to be a FACETS | 2018 | 3: 858-879 | DOI: 10.1139/facets-2018-0015 862 facetsjournal.com sink for MeHg. Together with previous work on methanogens, this finding frames methane cycling microbes as key players in controlling MeHg levels in the environment.…”
Section: Grégoire and Poulainmentioning
confidence: 84%
“…Along with Hg methylation, MeHg demethylation is likely to be a crucial determinant of net concentrations of MeHg, which had been well documented in the three compartments of the Everglades (31,34). Two pathways have been proposed for microbial MeHg demethylation: the reductive pathway that first cleaves MeHg to Hg(II) and CH 4 by an organomercurial-lyase enzyme encoded by merB and then to Hg(0) by mercuric reductase encoded by merA of Hg-resistant bacteria (46)(47)(48)(49)(50), as well as by the oxidative pathway that completely oxidizes MeHg to CO 2 and Hg(II) by SRP and methanogens (51)(52)(53)(54). More recently, a methanotroph was also reported to degrade MeHg via the potential activity of methanol dehydrogenase (55).…”
Section: Discussionmentioning
confidence: 99%
“…While many wetlands, including boreal peatlands, net‐produce and export MeHg to downstream environments (Tjerngren et al ., 2012b), it was recently established by input–output budgets that black alder ( Alnus glutinosa ) swamps are consistent MeHg sinks (Kronberg et al ., 2012; Tjerngren et al ., 2012a; Kronberg et al ., 2018). Because alder swamps are nutrient‐rich environments, they typically form in depressions and along edges of lakes and streams in the lower sections of boreal landscapes.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, alder swamps are most often situated downstream of major sources of MeHg, such as upland forest clear‐cuts (Kronberg et al ., 2016b) and nutrient poor peatlands (Kronberg et al ., 2012), but still upstream of most aquatic ecosystems, such as lakes and rivers. This means that the net MeHg degradation in alder swamps (Kronberg et al ., 2018) has the potential to play an important role in protecting aquatic biota from MeHg accumulation. While alder swamps support high MeHg demethylation rates, these wetlands also support high rates of MeHg production.…”
Section: Introductionmentioning
confidence: 99%